2014
DOI: 10.5194/bgd-11-17861-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Iron budgets for three distinct biogeochemical sites around the Kerguelen archipelago (Southern Ocean) during the natural fertilisation experiment KEOPS-2

Abstract: International audienc

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 127 publications
(222 reference statements)
6
34
0
Order By: Relevance
“…Unexpectedly, the highest DWA Ba xs value of the whole study area (572 pM; 150-400 m) was observed at the reference R-2 site. For R-2, Bowie et al (2014), Quéroué et al (2015) and van der Merve et al (2015) reported local maxima in particulate and dissolved trace metals at 500 m and deeper, reflecting lateral transport of lithogenic matter possibly originating from the Leclaire Rise (a large seamount located west of R-2). Similarly, observed a maximum of lithogenic silica (LSi) at 500 m, confirming lithogenic inputs there.…”
Section: Depth-weighted Average Ba Xs Content Of Mesopelagic Watersmentioning
confidence: 99%
“…Unexpectedly, the highest DWA Ba xs value of the whole study area (572 pM; 150-400 m) was observed at the reference R-2 site. For R-2, Bowie et al (2014), Quéroué et al (2015) and van der Merve et al (2015) reported local maxima in particulate and dissolved trace metals at 500 m and deeper, reflecting lateral transport of lithogenic matter possibly originating from the Leclaire Rise (a large seamount located west of R-2). Similarly, observed a maximum of lithogenic silica (LSi) at 500 m, confirming lithogenic inputs there.…”
Section: Depth-weighted Average Ba Xs Content Of Mesopelagic Watersmentioning
confidence: 99%
“…At all stations, seawater was collected with 10 L Teflon-lined Niskin-1010X bottles mounted on a 1018 rosette system adapted for trace-metal clean work (Bowie et al, 2014). Sampling depths (surface mixed layer) were 40 m at stations R2 and E-4W, 37 m at station E-3 and 25 m at station E-5.…”
Section: Experimental Designmentioning
confidence: 99%
“…In situ samples for dissolved organic carbon (DOC) analyses were taken with Teflon-lined Niskin-1010X bottles adapted for trace-metal clean work (Bowie et al, 2014). Seawater was filtered through two combusted GF/F (0.7 µm nominal pore size, Whatman) filters and 15 mL of the filtrate was stored acidified (H 3 PO 4 , final pH = 2) in combusted 20 mL glass ampoules at room temperature in the dark.…”
Section: Dissolved Organic Carbon Analysesmentioning
confidence: 99%
“…Seawater samples were collected with 10-L Niskin 1010X bottles set up on an autonomous model 1018 trace metal rosette especially adapted for trace metal work (General Oceanics Inc., USA; Bowie et al, 2014). Each Niskin bottle was acid-washed (2 % HCl) and rinsed with Milli-Q water before the rosette was deployed.…”
Section: Sampling and Manipulation Under Trace Metal Clean Conditionsmentioning
confidence: 99%